Relationship between personality type and learning motivation of students in grade X at Giovanni Catholic High School in Kupang in the 2024/2025 academic year - Maria Silvani Kupu Da; Rosa Mustika Bulor; Stefanus Lio (Edumaspul: Jurnal Pendidikan, 2025)
This research aims to determine the relationship between personality type and the learning motivation of class X students at the school. The type of research used is quantitative research with the independent variable (X), namely personality type, and the dependent variable (Y), namely learning motivation. The data collection technique uses a closed questionnaire, while data analysis is carried out using the Product Moment correlation formula with the help of the SPSS version 26 for Windows program. The results of the research show that there is a low but significant relationship between personality type and student learning motivation, with a correlation coefficient value of r = -0.358, which means it has a low level of relationship and a significance of p = 0.002 (p < 0.05), which means the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted.